ESG UNDERSTANDING BY MSME ACTORS IN MANAGERIAL DECISION MAKING (Study on Tofu Factory MSMEs) - Maudi _ Solehah (UNIVERSITAS DHARMAWANGSA, 2026)
This study aims to examine the understanding of Environmental, Social, and Governance (ESG) principles among Micro, Small, and Medium Enterprises (MSMEs) in managerial decision-making at a tofu manufacturing MSME in Tasikmalaya Regency. The study was motivated by the low level of MSME understanding regarding sustainability concepts, inadequate waste management practices, and managerial decisions that are still based on personal experience and traditional practices. This research employed a qualitative method with an exploratory approach. Data were collected through interviews, observations, and documentation involving several informants, including the business owner, production manager, employees, local community members, and representatives from the environmental agency. Data analysis was conducted through data reduction, data presentation, open coding, axial coding, and conclusion drawing. The results indicate that MSME actors do not formally understand the ESG concept; however, some ESG values have been indirectly implemented in daily business activities, particularly in the social aspect. In the environmental aspect, waste management practices remain simple and do not yet comply with environmental standards. In the social aspect, relationships between business owners, employees, and the surrounding community are relatively harmonious through communication and deliberation. Meanwhile, in the governance aspect, business records and managerial decision-making are still conducted in a simple manner based on experience. The main obstacles to ESG implementation include limited financial resources, lack of knowledge, and inadequate supporting facilities.